Mathematical modeling of the parasitism and hyperparasitism increase on Halyomorpha halys eggs in a five-year survey in Northern Italy - Ezio Venturino; Francesco Cantaloni; Luciana Tavella; Silvia Moraglio; Francesco Tortorici (Mathematical Biosciences and Engineering)
The invasive stink bug Halyomorpha halys has become an important pest of many crops, causing severe economic losses to farmers. Control of the pest mainly relies on multiple applications of broad-spectrum insecticides, undermining the integrated pest management programs and causing secondary pest outbreaks. In the native area, egg parasitoids are the main natural enemies of H. halys, among which Trissolcus japonicus is considered the predominant species. In Italy, adventive populations of T. japonicus and Trissolcus mitsukurii, another egg parasitoid of H. halys in Japan, have established themselves. These two species, together with the indigenous Anastatus bifasciatus, are capable of attacking the eggs of the exotic host. Focusing on the situation in Northern Italy, where also the hyperparasitoid Acroclisoides sinicus is present, a discrete-time model is developed for the simulation of the pest evolution. It is based on actual field data collected over a timespan of five years. The simulations indicate that egg parasitoid by themselves do not suppress populations to non-pest levels, but can play an important role in reducing their impact. Both the data from the five-year surveys and those available in the literature are used in the model. It has some limitations in the fact that climatic conditions were not considered, while more accurate simulations could be performed with additional collection of field data, which at the moment are based on partial field observations not sampled at the same sites.